Insights into the effect of iron-carbon particle amendment on food waste composting: Physicochemical properties and the microbial community. (May 2022) - He, Yingying; Huang, Xia; Zhang, Hongning; Li, Huiping; Zhang, Yidie; Zheng, Xiaomei; Xie, Li
Graphical abstract: Highlights: Fe-C enhanced organic matter degradation by 12.3%, especially lignocellulose. Fe-C promoted humus formation by 15.5%. Nitrification was enhanced by Fe-C for nitrogen retention. Bacillus and Aspergillus were key bacterial and fungal genera, respectively. Electrical conductivity was determined to play a key role in the fungal community. Abstract: The effects of iron-carbon (Fe-C) particle amendment on organic matter degradation, product quality and functional microbial community in food waste composting were investigated. Fe-C particles (10%) were added to the material and composted for 32 days in a lab-scale composting system. The results suggested that Fe-C particle enhanced organic matter degradation by 12.3%, particularly lignocellulose, leading to a greater humification process (increased by 15.5%). In addition, NO3 − -N generation was enhanced (15.9%) by nitrification with more active ammonia monooxygenase and nitrite oxidoreductase activities in the cooling and maturity periods. Fe-C particles not only significantly increased the relative abundances of Bacillus and Aspergillus for organic matter decomposition, but also decreased the relative abundances of acid-producing bacteria. RDA analysis demonstrated that the bacterial community was significantly influenced by dissolved organic matter, C/N, NO3 − -N, humic acid, volatile fatty acids and pH, while electrical conductivity was the key factor affecting the fungal community.